Peran Budaya Islami, Kedisiplinan Dan Kepemimpinan Terhadap Peningkatan Kinerja Pegawai Yayasan Lembaga Bakti Muslim Al-Falah Sragen Dengan Motivasi Sebagai Variabel Intervening - Ngadino Ngadino; Septiana Novita Dewi (ProBank, 2026)
This study aims to determine, analyze and provide significant empirical evidence directly and indirectly, the direct and indirect influence of the role of Islamic Culture, Discipline, and Leadership as well as motivation as intervening variables on employee performance at the Al-Falah Muslim Bakti Foundation, Sragen Regency. Data collection in this study using a questionnaire. The analysis method used is an instrument test which includes validity and reliability tests, linearity tests, path analysis t-tests, F-tests and coefficient of determination tests. The sample in this study was 50 employees of the Al-Falah Muslim Bakti Foundation, Sragen Regency, with the total sample method. The questionnaire test results were valid and reliable. Hypothesis testing results indicated that Islamic Culture had a positive and significant effect on employee performance. Discipline and Leadership had a positive but insignificant effect on employee performance at the Al-Falah Muslim Service Foundation in Sragen Regency. Path analysis results indicated that the direct influence of discipline and motivation was more effective than the indirect influence. The indirect influence of Islamic Culture on performance was the most effective pathway. A total R2 value of 0.459 indicates that 45.9% of the Islamic Culture variable at the Al-Falah Muslim Service Foundation in Sragen Regency can be explained by the Islamic Culture variable, with the remaining 54.1% explained by other variables outside the model. Meanwhile, a total R2 value of 0.64 indicates that the performance variable can be explained by 64% of the Islamic Culture, Discipline, and Leadership variables, with the remaining 36% explained by other variables in the model.